Mini-review. Perspective on biomass derived bio-oil valorization in Vietnam - Thuan, Huynh Minh; Long, Duong Thanh; Hung My, Nguyen Huynh; Quoc Binh, Phan Minh; Luong, Nguyen Huu (Vietnam Journal of Chemistry, 2017)
Various  strategies  for  biomass derived bio-oil valorization  as  a  renewable  feedstock  for  chemicals  and  fuels  are described.  Starting  from  the  role  of  renewable  resources  (e.g.  biomass,  bio-oil)  in  the  future  energy  and  chemical community, an overview on current energy supply situation and the role of biomass and related products are discussed. Later,  summary  of  bio-oil  production  from  biomass  and  the  need  for  upgrading  to  further  uses  is  represented. Subsequently,  the  valorization  of  bio-oil  as  fuels  and  feedstocks  are  intensively  summarized,  showing  the  potential utilization  of  bio-oils  via  such  processes.  Some  studies  on  biomass  assessment,  bio-oil  production  and  upgrading  in Vietnam  are  also  given.  Finally,  some  concluding  remarks  address  the  perspectives  for  further  research  and development to overcome future challenges.Keywords. Bio-oil valorization, bio-oil/diesel emulsion, co-feeding, deoxygenation, refinery units.